Comparison of Angiographic Severity between Patients of Acute Myocardial Infarction & Chronic Stable Angina Pectoris - Safiuddin, Mohammad; Uddin, Mir Jamal; Islam, Sirajul; Habib, SM Ahsan; Kauser, Mohammad Abu; Khan, Md Saif Ullah; Choudhury, Minhaj Rahim; Rahman, Fazlur; Safi, Shahnaj Binte (University Heart Journal, 2012)
A prospective randomized cohort study was done in 100 patients and the study population consisted 50 patients with unheralded acute myocardial infarction and 50 with uncomplicated stable angina pectoris. The main objectives of the study were to compare the angiographic severity between the two clinical subsets of IHD. The study observed that regarding number of vessels diseased , the AMI group had 1.52±0.68 compared with 2.37±0.85 vessels for the angina group reflecting significantly higher diseased vessel in latter group (P<0.001). In comparison with unheralded AMI, the stable angina group had greater number of stenoses(4.16±1.9 vs 2.14±1.5, P<0.001) and also greater number of occlusions(0.80±0.65 vs 0.44±0.31, P<0.001 ). Thus from the above data it is clear that single vessel disease is more frequent in AMI group and double- and tripple vessel diseases are more prevalent in angina group and fewer stenoses and discrete type of lesions in the former and more number of diseased vessels, more stenoses, and diffuse type of lesions in the latter. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11659 University Heart Journal Vol. 8, No. 1, January 2012